Institutional Review Boards: - Alvita K. Nathaniel (Grounded Theory Review: An International Journal)
In the U.S., all research must be approved by an Institutional Review Board (IRB) that evaluates research protocols for the purpose of protecting human subjects. This paper includes a brief history of the development of public policy that guides institutional review boards in the U.S. and commentary on the responsibilities of a grounded theory researcher interested in applying for approval for a research study.